2021
DOI: 10.3344/kjp.2021.34.4.471
|View full text |Cite
|
Sign up to set email alerts
|

The association between pain, balance, fall, and disability in patients with lumbar spinal stenosis with vascular claudication

Abstract: Background The effect of lumbar spinal stenosis (LSS) and peripheral vascular disease (PVD), which occurs with similar degenerative conditions, when seen together, has not been studied. The aim of this study is to examine and compare the relationship between pain, balance, disability, fear of falling, and kinesiophobia in LSS patients with intermittent vascular claudication (IVC). Methods Seventy-two patients diagnosed with LSS using magnetic resonance imaging participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
(86 reference statements)
1
5
0
Order By: Relevance
“…This study found a correlation between balance and PAD (OR=1.058, 95% CI=1.007-1.112) in older people. This was consistent with the results of previous studies 37,38) . The TUGT has been endorsed by the US Centers for Disease Control and Prevention as a clinically useful tool for evaluating gait, strength, and balance in determining fall risk in elderly patients 39) .…”
Section: Relationship Between Balance and Padsupporting
confidence: 94%
“…This study found a correlation between balance and PAD (OR=1.058, 95% CI=1.007-1.112) in older people. This was consistent with the results of previous studies 37,38) . The TUGT has been endorsed by the US Centers for Disease Control and Prevention as a clinically useful tool for evaluating gait, strength, and balance in determining fall risk in elderly patients 39) .…”
Section: Relationship Between Balance and Padsupporting
confidence: 94%
“…Second, several different methods have been shown to be effective in discriminating spinal stenosis to evaluate lumbar spinal stenosis, such as sedimentation sign and morphologic grade system. [23][24][25][26][27][28][29][30] However, we only measured CLFT and LLFT. Thus, our research might have some limitations regarding measurement of morphologic change and epidural pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers analyzed the medical data from patients aged 60-92 years who had axial and radicular pain from LSS and were given either mechanical needling with sterile water injection or lidocaine injection. The following symptoms were used to diagnose patients with LSS: (1) having leg or buttock pain while walking; (2) flexing forward to relieve symptoms; (3) feeling relief when using a shopping cart or bicycle; (4) having motor or sensory disturbance while walking; (5) the pulses in the foot are present and symmetric; (6) have lower extremity weakness and decreased walking ability; (7) have low back pain. Patients were then selected to be recruited if there were the following signs: (1) Kemp's sign, (2) induced pain in the articular or transverse apophysis, and (3) sign of facet tension or new lumbar facet sign.…”
Section: Participantsmentioning
confidence: 99%
“…Facet joint hypertrophy is a condition which the cartilage between the inferior and superior articular processes breaks down and becomes inflamed, causing pain signals to be sent to the innervated medial branch nerve endings. [6][7][8][9][10][11] The L4-L5 region of the lumbar spine is the most prevalent site of LSS. 7,[9][10][11][12][13] Radicular pain in spinal stenosis is caused by inflammation or compression of the spinal nerve root, with disc herniation being the most prevalent cause.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation